2022
DOI: 10.1002/admt.202101715
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Thermoelectric Properties of Boron‐Doped Silicon Nanowires Integrated into a Micro‐Harvester

Abstract: The data that support the findings of this study are openly available in Thermoelectric properties of p-doped rough silicon nanowires at https://doi.org/10.5281/zenodo.5806683, reference number 1194.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…The result is consistent with studies relating the degree of surface roughness with an enhanced phonon scattering. [41,42] The value also matches 𝜅 estimations performed using fully electrical measurements [26] in the same kind of wires and is also consistent with the theoretical predictions for rough NWs [43][44][45] employing again a fully diffuse model (specularity parameter p = 0) and estimated surface-to-volume ratios in the order of 0.015 nm −1 .…”
Section: Thermal Conductivity Determinationsupporting
confidence: 86%
See 1 more Smart Citation
“…The result is consistent with studies relating the degree of surface roughness with an enhanced phonon scattering. [41,42] The value also matches 𝜅 estimations performed using fully electrical measurements [26] in the same kind of wires and is also consistent with the theoretical predictions for rough NWs [43][44][45] employing again a fully diffuse model (specularity parameter p = 0) and estimated surface-to-volume ratios in the order of 0.015 nm −1 .…”
Section: Thermal Conductivity Determinationsupporting
confidence: 86%
“…The NW studied in this work is expitaxially integrated at both ends in the same way as those NWs reported in prior works, [ 21,25,26 ] as illustrated in Figure a. The NW has a length of 17.3 µm, an average diameter of 57.2 nm, and it is suspended at a distance of 2.5 µm over the substrate (see Figure , Supporting Information).…”
Section: Resultsmentioning
confidence: 97%
“…[ 50 ] Contrary, the observed reduction is likely related to the suppression of the phonon drag contribution driven by the nanostructuration which doubtlessly affects the thermal conductivity. This effect is not expected to be as important as in the case of pure silicon [ 51–53 ] since germanium alloying already induces an important phonon suppression enhancement. However, it might still contribute to this reduction at the low‐temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…Because at the scales of the studied NW (Φ NW ≈ 87 nm) no alteration of the electronic structure is expected -typically happening for Φ NW < 10 nm -size effects can be discarded as responsible for the observed reduced S. [50] Contrary, the observed reduction is likely related to the suppression of the phonon drag contribution driven by the nanostructuration which doubtlessly affects the thermal conductivity. This effect is not expected to be as important as in the case of pure silicon [51][52][53] since germanium alloying already induces an important phonon suppression enhancement. However, it might still contribute to this reduction at the low-temperature range.…”
Section: Thermoelectrical Propertiesmentioning
confidence: 97%
“…[135][136][137] High concentrations of phosphorous (n-type) and boron (p-type) dopants have been frequently used to increase phonon scattering for lower thermal conductivity and increase charge carriers for higher PFs. [41,[138][139][140] Liu et al [17] found that increasing phosphorus doping in a GaP/Si composite 2 stoichiometric percentage to 5 stoichiometric percentage increased electrical conductivity by 30% and decreased thermal conductivity by 40%. The phosphorus increased the carrier concentration and [120] Copyright 2017, Elsevier.…”
Section: Siliconmentioning
confidence: 99%